Principles of Justice, Conference and Legal Accountability in Divorce Rules - Masri Olii (International Journal of Nusantara Islam, 2020)
The Religious Courts, in the last decade (since 2005) or since the implementation of the one roof system of judiciary, have made various improvements in the administration of justice to support efforts to reform the judiciary based on the principles of transparency and accessibility for all. the justice seeker. The Religious Courts are trying to reform several sub-systems in the judicial system that have so far not reflected equal access for justice seekers as well as protection or partiality for the rights and legal access of women, children, and the poor. The results of this study indicate that: the religious court is a place to seek justice and resolve Islamic family law problems, so in providing services to the community, it has the main task of providing fair and humane treatment to justice seekers, providing sympathetic services and assistance needed for justice seekers, and provide effective, efficient, thorough and final settlement of cases so as to satisfy the public.